2015
DOI: 10.1128/aem.00444-15
|View full text |Cite
|
Sign up to set email alerts
|

LA35 Poultry Fecal Marker Persistence Is Correlated with That of Indicators and Pathogens in Environmental Waters

Abstract: bDisposal of fecally contaminated poultry litter by land application can deliver pathogens and fecal indicator bacteria (FIB) into receiving waters via runoff. While water quality is regulated by FIB enumeration, FIB testing provides inadequate information about contamination source and health risk. This microbial source tracking (MST) study compared the persistence of the Brevibacterium sp. strain LA35 16S rRNA gene (marker) for poultry litter with that of pathogens and FIB under outdoor, environmentally rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Agricultural production practices, both crop and animal, have been identified as sources of excess nutrients and microorganisms contributing to freshwater pollution (Nayak et al, 2015;Evans et al, 2019). In states such as Arkansas, the land application of manure generated by confined poultry operations has been identified as a source of both excess nutrients, especially phosphorous, and fecal indicator bacteria (FIB) in regional watersheds (Ismail et al, 2016;Sharpley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural production practices, both crop and animal, have been identified as sources of excess nutrients and microorganisms contributing to freshwater pollution (Nayak et al, 2015;Evans et al, 2019). In states such as Arkansas, the land application of manure generated by confined poultry operations has been identified as a source of both excess nutrients, especially phosphorous, and fecal indicator bacteria (FIB) in regional watersheds (Ismail et al, 2016;Sharpley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Li et al (2015) reported relatively low sensitivity of the LA35 marker when applied to poultry litter samples, although the authors did not compare with the CL marker or any other poultry‐specific marker. Unfortunately, additional studies using the LA35 poultry marker did not apply the marker to environmental waters, but rather to experimental microcosms to evaluate persistence (Nayak et al, 2015; Mantha et al, 2017). Therefore, this is the first study to evaluate both poultry‐specific markers within a single watershed over a prolonged period of time.…”
Section: Resultsmentioning
confidence: 99%
“…; Nayak et al . ). As elevated fecal indicator bacteria (FIB) levels have been correlated with an increased human risk of illness (Prüss ), the microbiological quality of water has been assessed for decades by enumerating FIB such as Escherichia coli ( E. coli ) and enterococci in recreational waters (USEPA ).…”
Section: Introductionmentioning
confidence: 97%